Aldose Reductase, Oxidative Stress, and Diabetic Mellitus - Tang, Waiho; Martin, Kathleen A.; Hwa, John (Frontiers in Pharmacology, 2012)
Diabetes mellitus (DM) is a complex metabolic disorder arising from lack of insulin production or insulin resistance 1. DM is a leading cause of morbidity and mortality in the developed world, particularly from vascular complications such as atherothrombosis in the coronary vessels. Aldose reductase (AR) [ALR2; EC 1.1.1.21], a key enzyme in the polyol pathway, catalyzes NADPH-dependent reduction of glucose to sorbitol, leading to excessive accumulation of intracellular reactive oxygen species (ROS) in various tissues of DM including the heart, vasculature, neurons, eyes and kidneys. As an example, hyperglycemia through such polyol pathway induced oxidative stress, may have dual heart actions, on coronary blood vessel (atherothrombosis) and myocardium (heart failure) leading to severe morbidity and mortality (reviewed in 2). In cells cultured under high glucose conditions, many studies have demonstrated similar AR-dependent increases in ROS production, confirming AR as an important factor for the pathogenesis of many diabetic complications. Moreover, recent studies have shown that AR inhibitors may be able to prevent or delay the onset of cardiovascular complications such as ischemia/reperfusion injury, atherosclerosis and atherothrombosis. In this review, we will focus on describing pivotal roles of AR in the pathogenesis of cardiovascular diseases as well as other diabetic complications, and the potential use of AR inhibitors as an emerging therapeutic strategy in preventing DM complications.